Improving User Interaction on Ontology-based Peer Data Management Systems - Alencar, Andreza Leite de; Salgado, Ana Carolina (iSys - Brazilian Journal of Information Systems, 2014)
The issue of user interaction for query formulation and execution has been investigated for distributed and dynamic environments, such as Peer Data Management System (PDMS). Many of these PDMS are semantic based and composed by data peers which export schemas that are represented by ontologies. In the literature we can find some proposed PDMS interfaces, but none of them addresses, in a general way, the needs of a PDMS for user interaction. In this work we propose a visual user query interface for ontology-based PDMS. It provides a simple and straightforward interaction with this type of system. It aims not only providing a natural visual query interface but also supporting a precise and direct manipulation of the data schemas for query generation.